MENINGKATKAN SIKAP TANGGUNG JAWAB DAN PRESTASI BELAJAR MELALUI MODEL PEMBELAJARAN TIPE NUMBER HEAD TOGETHER (NHT) BERBANTU VIDEO STOP MOTION - Meilyyana Cahya Pramestika; Arifin Muslim; Karma Iswasta Eka (STKIP Melawi, 2019)
Abstract: The background of this research is a phenomenon of the low of students’ responsibility attitude and learning achievement. The research is aimed to improve students’ responsibility attitude and learning achievement through learning model number head together (NHT) with stop motion video. The class action research was consisting of planning, implementation, observation and reflection steps. The subjects of this research were on sixth grade students of elementary school Susukan, with the total numbers were 24 students. The research instruments used were evaluation test, observation sheet and questionnaire. The finding showed there was an improvement of each cycle. The result of this research showed that the using of the learning model numbered head together (NHT) could improve student’ responsibility attitude and learning achievement in theme 9 “Kayanya Negeriku” on the sixth grade students of elementary school Susukan, Wanayasa district, Banjarnegera.Keywords: Responsibility’ Manner, Learning Achievement, Numbered Head Together (NHT) Abstrak: Penelitian ini dilatar belakangi oleh rendahnya sikap tanggung jawab dan prestasi belajar peserta didik. Penelitian ini bertujuan meningkatkan sikap tanggung jawab dan prestasi belajar melalui model pembelajaran Numbered Head Together (NHT) berbantu video stop motion. Penelitian tindakan kelas terdiri dari tahapan perencanaan, pelaksanaan, observasi dan refleksi. Subjek penelitian adalah peserta didik kelas IV SDN Susukan, berjumlah 24 peserta didik. Alat pengumpulan data menggunakan tes evaluasi, lembar observasi dan angket. Hasil penelitian menunjukan peningkatan disetiap siklus. Hasil penelitian ini menunjukan bahwa penggunaan model pembelajaran Numbered Head Together (NHT) dapat meningkatkan sikap tanggung jawab dan prestasi belajar pada tema 9 Kayanya Negeriku di Kelas IV SDN Susukan, Kecamatan Wanayasa, Banjarnegara.Kata Kunci: Sikap Tanggung Jawab; Prestasi Belajar; Numbered Head Together (NHT)